1997
DOI: 10.1159/000244491
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hyperglycemia on Gasping and Autoresuscitation in Newborn Rats

Abstract: The aim of this study was to test the effects of glucose on the gasping ability and survival in a rat pup model during acute anoxia. Newborn rat pups of both 1 and 8 days of age were given glucose (30 and 60 mg/animal) or saline intraperitoneally and subsequently subjected to anoxia (100% N2). Glucose supplement induced hyperglycemia. Respiration was recorded by barometric plethysmography. The rat pups responded to acute anoxia with a robust sequence of respiratory pattern: hyperpnea, primary apnea,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
11
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 16 publications
(28 reference statements)
4
11
0
Order By: Relevance
“…Therefore, our current experiments were carried out at thermoneutrality to minimize deviations in basal core temperature from normal in this altricial species, which has a limited ability to regulate its core temperature when exposed to ambient temperatures outside its thermoneutral zone (29,33). On exposure to a single period of hypoxia, our rat pups exhibited a triphasic gasping pattern following primary apnea as has been previously shown to occur by others in newborn rats (21,44) and rabbits (6, 28) but not in mice (25). This triphasic gasping pattern consisted of an initial phase of rapid gasping (phase I) that was followed by a second phase of slower gasping (phase II); finally there was a third phase of rapid gasping (phase III), which eventually waned and gave way to terminal or secondary apnea and death.…”
Section: Discussionsupporting
confidence: 77%
“…Therefore, our current experiments were carried out at thermoneutrality to minimize deviations in basal core temperature from normal in this altricial species, which has a limited ability to regulate its core temperature when exposed to ambient temperatures outside its thermoneutral zone (29,33). On exposure to a single period of hypoxia, our rat pups exhibited a triphasic gasping pattern following primary apnea as has been previously shown to occur by others in newborn rats (21,44) and rabbits (6, 28) but not in mice (25). This triphasic gasping pattern consisted of an initial phase of rapid gasping (phase I) that was followed by a second phase of slower gasping (phase II); finally there was a third phase of rapid gasping (phase III), which eventually waned and gave way to terminal or secondary apnea and death.…”
Section: Discussionsupporting
confidence: 77%
“…In our experience, gasping occurs within 60 -90 s of the onset of hypoxia, and naive 5-to 6-day-old rat pups may gasp up to 15 min and exhibit as many as 86 potential autoresuscitation producing gasps. Our laboratory and others have shown that one or more of the previously mentioned gasping characteristics are modulated in this age range of rat pups by factors such core temperature (28), glucose (44), catecholamines (45), nitric oxide (13), and glutamate (12). Given that all of these factors may be altered in one way or the other by exposure to hypoxia, our present experiments have been carried out to determine whether prior exposure to hypoxic-induced apnea, such as may occur during prolonged obstructive apnea or positional asphyxia, influences gasping on exposure to unrelenting hypoxia.…”
mentioning
confidence: 67%
“…Although the mechanism of the altered gasping pattern after prior exposure to hypoxic-induced apnea is unknown, it may have resulted from substrate depletion, altered neuroendocrine function, or synthesis and release of neuromodulators that influence hypoxic gasping. As previously mentioned, a number of factors have been shown to govern the time to last gasp in rats during early postnatal development on exposure to unrelenting hypoxia including core temperature (28), glucose (37,44), catecholamines (45), excitatory amino acids (12), and nitric oxide (13). Our laboratory has previously shown that exposure to hypoxia induces a "regulated" decrease in core temperature (3) and that core temperature influences the time to last gasp as well as the total number of gasps in 5-to 6-day-old rat pups on exposure to unrelenting hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, depletion of cardiac glycogen with recurrent autoresuscitations was advanced as one of the mechanisms potentially leading to autoresuscitation failure in the usually successful autoresuscitating BALB/c mice (3). However, external fuel delivery as brought about by glucose supplementation before the asphyxic exposure exerts divergent effects on gasping and autoresuscitation (28). Indeed, Yuan and colleagues (28) have shown that hyperglycemia will prolong the overall duration of gasping but reduce the frequency of autoresuscitation.…”
Section: Discussionmentioning
confidence: 99%
“…However, external fuel delivery as brought about by glucose supplementation before the asphyxic exposure exerts divergent effects on gasping and autoresuscitation (28). Indeed, Yuan and colleagues (28) have shown that hyperglycemia will prolong the overall duration of gasping but reduce the frequency of autoresuscitation. Yuan et al (29) also examined the role of adrenergic receptors, and found that adrenalectomy shortened gasping duration in both 1-day-old and 8-day-old rats, whereas the nonselective ␣-receptor antagonist phentolamine reduced the duration of gasping in 1-day-old rats but prolonged this duration in 8-day-old rats, with similar effects on gasping by the nonselective ␤-receptor antagonist propranolol.…”
Section: Discussionmentioning
confidence: 99%